Viltanpassad röjning längs skogsbilvägar som en foderskapande åtgärd för älgen - Forslund, Ida (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2012)
The moose is a keystone species in the boreal forest ecosystem, but the dense Swedish population do cause some serious problems. From a forestry perspective, their browsing on young Scot pine (Pinus sylvestris) causes extensive losses of revenue. Adjusting the cleaning along roadsides of low trafficked forest roads can favour the production of plant species preferred by the moose. This is thought to redirect the moose´s browsing to the roadsides and thereby decrease the damages on commercial forest.